2016
DOI: 10.1038/srep34975
|View full text |Cite
|
Sign up to set email alerts
|

The chitin synthase FgChs2 and other FgChss co-regulate vegetative development and virulence in F. graminearum

Abstract: Fusarium graminearum contains eight chitin synthase (Chs) genes belonging to seven classes. Previous studies have found that deletion of FgChs3b is lethal to F. graminearum, and deletion of FgChs1, FgChs2, FgChs7 and FgChs5 caused diverse defects in chitin content, mycelial growth, conidiation, virulence or stress responses. However, little is known about the functional relationships among these FgChss. In this study, FgChs2 deletion mutant ΔFgChs2 exhibited reduced mycelial growth and virulence as reported pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 52 publications
(94 reference statements)
1
26
0
Order By: Relevance
“…Our results indicated that PcCHS and PsCHS1 , but not PsCHS2 , have functions in regulating mycelial growth, sporangial production and zoospore release, as well as zoospore germination and hyphal branch formation during early infection. As is true of certain fungal CHS genes (Kong et al ., ; Cheng et al ., ; Liu et al ., ), we suggest that PcCHS and PsCHS1 play critical roles during normal vegetative growth, propagation and pathogenicity in P. capsici and P. sojae . Although vegetative growth and reproduction were retarded in the Δ PcCHS and Δ PsCHS1 mutants, we found no obvious morphological hyphal abnormality (swelling and/or distortion) under the microscope.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results indicated that PcCHS and PsCHS1 , but not PsCHS2 , have functions in regulating mycelial growth, sporangial production and zoospore release, as well as zoospore germination and hyphal branch formation during early infection. As is true of certain fungal CHS genes (Kong et al ., ; Cheng et al ., ; Liu et al ., ), we suggest that PcCHS and PsCHS1 play critical roles during normal vegetative growth, propagation and pathogenicity in P. capsici and P. sojae . Although vegetative growth and reproduction were retarded in the Δ PcCHS and Δ PsCHS1 mutants, we found no obvious morphological hyphal abnormality (swelling and/or distortion) under the microscope.…”
Section: Discussionmentioning
confidence: 99%
“…In Fusarium graminearum , which contains eight CHS genes, deletion of FgCHS3b is lethal to the fungus, whereas deletion of FgCHS1 , FgCHS2 , FgCHS7 or FgCHS5 variously affects chitin content, mycelial growth, conidiation, virulence or stress responses. However, deletion of FgCHS3a , FgCHS4 or FgCHS6 did not seem to have any effects (Xu et al ., ; Cheng et al ., ; Liu et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Because DON plays an important role in the extension of F . graminearum inside the hosts (Liu et al, ), we reasoned the inability of the FgAP‐2 deletion mutants to cause severe disease symptoms in the host is largely due to their slow growths.…”
Section: Discussionmentioning
confidence: 99%
“…Normal mycelial growth is crucial to ensure fungal vitality and other activities (Cota et al, 2008;Liu et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Normal mycelial growth is crucial to ensure fungal vitality and other activities ( Cota et al, 2008 ; Liu et al, 2016 ). In our current study, ΔCrSsd1 deletion mutants exhibited reduced hyphal growth, suggesting diverse functions for CrSsd1 in different fungal pathogens.…”
Section: Discussionmentioning
confidence: 99%